Can Creative Hubs Contribute Towards Creative City Development? Case of Hin Bus Depot, Penang, Malaysia - Khoo, Suet Leng; Chang, Nicole Shu Fun (Journal of Urban Culture Research, 2025)
As cities shift their economic base towards culture and creativity, the emergence of creative hubs to catalyze local creative industries is acknowledged as a viable urban development strategy. In Malaysia, the concept is not new. In George Town, Penang, a sterling example is Hin Bus Depot which is a once-abandoned bus depot that reinvented itself to become a successful creative community hub. The ways upon which Hin contributes towards creative city development warrants documentation. Through qualitative techniques and a longitudinal timeframe, this paper unpacks Hin’s role by revisiting its evolving functionalities, forms, and meanings as it thrives, and responds to changes. Findings indicate that Hin is an organically self-gentrified creative hub that managed to stimulate socio-economic growth within the hub, and also its surrounding neighborhood. The findings further implicate creative hub concepts, policy and practice as George Town aspires to be a sustainable and inclusive creative city.